PEMBERDAYAAN KADER PKK UNTUK MELESTARIKAN BUDAYA MELALUI KETERAMPILAN BATIK TULIS - Rif’atul Laily; Afprida Masyitho; Muhammad Ihsan Misbah Khudin; Galuh Kartika Dewi; Ery Rahmawati; Anggra Lita Sandra Dewi (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2024)
Community service was carried out in becirongengor village, wonoayu district, Sidoarjo regency. This service aims to empower mothers to have batik skills. Batik is an Indonesian cultural heritage that has been recognized by the world, therefore efforts to empower the community must continue to be carried out. Batik is a cultural heritage that must continue to be preserved, One of the efforts in preserving by providing batik training, this is an attraction in improving the skills of PKK cadres. The method carried out in this research uses demonstration and training methods. The results of the training resulted in the participants being able to produce batik cloth works according to what was drawn.